Implementasi standar kompetensi lulusan dalam sistem penjaminan mutu sekolah di sekolah Islam berasrama: Implementation of graduate competency standards in the school quality assurance system at Islamic boarding schools - Fadhilah, Rizkia; Rahayu, Dede; Sya’dudin, Muhammad; Atiah, Umi (Epistemic: Jurnal Ilmiah Pendidikan, 2025)
Education in the era of globalization requires not only academic mastery, but also 21st-century skills that include character competencies, critical thinking skills, and life skills. In the context of education in Indonesia, Graduate Competency Standards (SKL) are the foundation for ensuring graduates have adequate attitudes, knowledge, and skills. Effective implementation of SKL must be integrated with the Internal Quality Assurance System (SPMI) to ensure sustainable education quality. Utsman bin Affan Boarding School adopts a unique approach by integrating the general education curriculum based on the Merdeka Curriculum, the Islamic boarding school curriculum, and project-based character and skills development programs (life skills). This study uses a qualitative approach with a case study design, which aims to explore and describe internal quality assurance practices at Utsman bin Affan Islamic Boarding School, especially in terms of Graduate Competency Standards. This study aims to evaluate the implementation of Graduate Competency Standards in the Internal Quality Assurance System (PMI) at Utsman bin Affan Boarding School. Specifically, this study seeks to identify the challenges faced, the strategies implemented, and the impact of SKL implementation on the quality of graduates produced.